Analisis Pengaruh Kurs Dollar Amerika Serikat, Inflasi dan Penanaman Modal Asing Terhadap Nilai Ekspor Makanan dan Minuman di Indonesia - Juliantari, Desak Putu Emmei; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 12, Desember 2015 (pp. 1445-1529), 2015)
Indonesia is a developing country, which can not be separated from international trade one of which is exported. Export activity is expected to increase the national income, one of the leading industrial products exported are food products and beverage s. This research analysis the influence of independent variables AS exchange rate, inflation and foreign direct investment simultaneously and partially toward dependent variables namely food and beverage export in Indonesian. The data analysis result indicate that exchange rate, inflation and foreign direct investment simultaneously have significant influence toward food and beverage export in Indonesia. This study used  secondary data. Data collectiaon to used by non participant observations. Method of data to used by studying to the descriptions of books, articles, thesis and journal as well as through the relevant agencies. Then the data is process by multiple linear regression analysis techniques that were proviously equipped with the classic asumtion with the program used is Eviews 6. Inflation no significant influence toward food and beverage export, the exchange rate and foreign direct investment is found to have positive significant influence toward food and beverage export in Indonesian.
Keywords: export; AS exchange rate; inflation; foreign direct investment